STOCK VALUATION AND FINANCIAL ANALYSIS ON PT BUKIT ASAM DURING INDONESIA'S COAL EXPORT BAN POLICY IN 2022 - Syafitri, Riza
The demand for coal in Indonesia and globally has risen in response to global population growth. Indonesia has relied heavily on coal as a primary fossil fuel and a vital element of its energy strategy since the 1970s. Indonesia is the largest exporter of thermal coal globally, having exported around 434 Mts in 2021. Its primary consumers include India, China, Japan, and South Korea.